A novel Kaizen technique for service quality: case study in educational organization. Issue 4 (10th April 2018) - Chen, Jih Kuang
Abstract : Purpose: The development and application of systematic procedures enabling Kaizen methodology development are still very rare, especially in the service industry. The purpose of this paper is to suggest a set of innovative improvement methodologies of service quality to enhance the extent and depth of Kaizen in the service domain. Design/methodology/approach: Combining the importance-performance analysis (IPA) method with impact matrix cross-reference multiplication applied to a classification (MICMAC), which is more convenient in calculation and application, and Fuzzy theory not only effectively integrates opinions of multiple experts, but also improves the conventional MICMAC method, which can only make binary judgment on the mutual influence of elements, by making it able to judge the degree of influence, thereby delivering more accuracy in evaluating the results. Findings: This innovative method which integrates Fuzzy-MICMAC with IPA displayed its usability in the analysis and research of a certain university library on service quality, and significant differences were found on comparing it with the conventional IPA method. The comparison and suggestion were proposed. Research limitations/implications: The number of the experts involved and samples under investigation were limited, hence findings were not comprehensive enough and cannot be generalized. This sets the direction for future research. Originality/value: This proposed method helps in overcoming the lack of systematic procedures enabling Kaizen methodology for service quality. It has the advantage of integrating existing tools and models effectively, which not only improve the shortcomings of the conventional methods, but also result in more convenient calculation and application, to promote Kaizen in service domain.